2013
DOI: 10.1155/2013/343804
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Curcuma longa L. Essential Oil and Curcumin on Aspergillus flavus Link Growth and Morphology

Abstract: The essential oil from Curcuma longa L. was analysed by GC/MS. The major components of the oil were ar-turmerone (33.2%), α-turmerone (23.5%) and β-turmerone (22.7%). The antifungal activities of the oil were studied with regard to Aspergillus flavus growth inhibition and altered morphology, as preliminary studies indicated that the essential oil from C. longa inhibited Aspergillus flavus Link aflatoxin production. The concentration of essential oil in the culture media ranged from 0.01% to 5.0% v/v, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 25 publications
2
19
1
1
Order By: Relevance
“…For example, adding 250 µL mL −1 of cumin phenolic extracts to SGM medium caused a radial growth increment (47.8%), OTA reduction (37.3%), and the cultures were dominated by the presence of white mycelium. These transformations were observed by Ferreira et al [ 41 ] who found that the use of curcumin EO at 1% on A. flavus cultures did not only reduce sporulation by 95.78%, but also decreased the viability of the remaining spores to 100%. A. parasiticus manifested the same results when it was cultured with thyme’s EO.…”
Section: Discussionsupporting
confidence: 55%
“…For example, adding 250 µL mL −1 of cumin phenolic extracts to SGM medium caused a radial growth increment (47.8%), OTA reduction (37.3%), and the cultures were dominated by the presence of white mycelium. These transformations were observed by Ferreira et al [ 41 ] who found that the use of curcumin EO at 1% on A. flavus cultures did not only reduce sporulation by 95.78%, but also decreased the viability of the remaining spores to 100%. A. parasiticus manifested the same results when it was cultured with thyme’s EO.…”
Section: Discussionsupporting
confidence: 55%
“…Some fungitoxic substances were already identified in mentrasto Esper et al, 2014), rue (Domingues et al, 2009;Azizi & Karouei, 2012), ginger (Sharma & Tiwari, 2013), false saffron (Ferreira et al, 2013;Parveen et al, 2013), citronella (Simic et al, 2008), rosemary (Ozcan & Chalchat, 2008), neem (Coventry & Allan, 2001) and eucalyptus citriodora (Aguiar et al, 2014). It is likely that fungicidal substances of wide spectrum present in the extracts and essential oils of these plants are involved in the inhibition of S. cepivora, such as precoceno in mentrasto , citronellal in citronella and eucalyptus citriodora (Simic et al, 2008;Tomazi et al, 2014), 1.8-cineole (eucalyptol) in ginger and rosemary (Ozcan & Chalchat, 2008;Sharma & Tiwari, 2013) and azadirachtin in neem (Coventry & Allan, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…In relation to the phenolic compounds, they have been reported to have toxic activities against fungi involved in the deterioration of agricultural products by interfering with the development of mycelia [ 49 ]. They affect membrane functions such as electron transport, nutrition, enzyme activity, protein and nucleic acid synthesis, and they interact with membrane proteins, causing disruption of the structures and functionality.…”
Section: Discussionmentioning
confidence: 99%